Book Reviews: Can China Lead the New World? - Walle, Alf (Journal of Applied Business and Economics, 2020)
Can China Rule the New World is a timely book that raises profoundly essential issues regarding China’s growing economic power and its evolving spheres of influence. The mission of the book is to present views that are held by contemporary Chinese leaders, strategists, and intellectuals. Westerners have long complained about the “guile of the Orient.” This book provides an analysis that can help the Western reader to understand better the Chinese people, who Westerners have often considered to be mysterious and unpredictable. It also provides a useful commentary regarding contemporary Chinese thinking and strategies along with a discussion of their implications to politics and economics.